2004
DOI: 10.1177/070674370404900108
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Women at Risk for Postnatal Depression Using the Edinburgh Postnatal Depression Scale at 2 to 3 Days Postpartum

Abstract: The EPDS completed at 2 to 3 days postpartum is a useful means of detecting women at risk of postnatal depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(79 citation statements)
references
References 10 publications
3
71
1
4
Order By: Relevance
“…Consistent with previous research (3)(4)(5)(6)37), nearly 80% of women with elevated EPDS scores at 8 weeks postpartum also had elevated scores in the immediate postpartum period. The variables that differentiated the women with new-onset symptoms of depression from those with persistent symptoms were very similar to the variables identified in the previous analysis of true-and false-positive scores.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous research (3)(4)(5)(6)37), nearly 80% of women with elevated EPDS scores at 8 weeks postpartum also had elevated scores in the immediate postpartum period. The variables that differentiated the women with new-onset symptoms of depression from those with persistent symptoms were very similar to the variables identified in the previous analysis of true-and false-positive scores.…”
Section: Discussionsupporting
confidence: 88%
“…As in other studies, our study has also found that immediate postpartum depressive symptoms on the continuous scale of EPDS overall correlates with the follow up scores [12][13]. The results are however, differed from a study that found a substantial drop in rates of depressive symptoms at eight weeks follow-up14.…”
Section: Discussionsupporting
confidence: 51%
“…The results are however, differed from a study that found a substantial drop in rates of depressive symptoms at eight weeks follow-up14. Similarly, a Canadian study suggests that only about 30 percent of those who have significant depressive symptoms at baseline continue to have high scores at four to six weeks of follow-up [13]. Though the women who followed up were similar to those who did not in many of the characteristics, selective follow-up of those remaining depressed cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, MacMahon et al (2005) found that 60% of women identified as being depressed at 4 months are still clinically depressed 1 year after delivery. In the development of postpartum depression, the predictive power of maternal mood during the immediate postpartum period has consistently been reported (Hannan et al, 1992;Dennis, 2004;Teissedre & Chabrol, 2004). Hannan et al (1992) noted a significant correlation between the mother's affective state on the fifth day postpartum and at 6 weeks both measured using the Edinburgh Postnatal Depressive Scale (EPDS).…”
Section: Introductionmentioning
confidence: 95%